Endoplasmic Reticulum Is at the Crossroads of Autophagy, Inflammation, and Apoptosis Signaling Pathways and Participates in the Pathogenesis of Diabetes Mellitus - Jing Su; Lei Zhou; Xiaoxia Kong; Xiaochun Yang; Xiyan Xiang; Yu Zhang; Xiaoning Li; Liankun Sun (Journal of Diabetes Research)
Diabetes mellitus (DM) is a chronic metabolic disease, and its incidence is growing worldwide. The endoplasmic reticulum (ER) is a central component of cellular functions and is involved in protein folding and trafficking, lipid synthesis, and maintenance of calcium homeostasis. The ER is also a sensor of both intra- and extracellular stress and thus participates in monitoring and maintaining cellular homeostasis. Therefore, the ER is one site of interaction between environmental signals and a cell’s biological function. The ER is tightly linked to autophagy, inflammation, and apoptosis, and recent evidence suggests that these processes are related to the pathogenesis of DM and its complications. Thus, the ER has been considered an intersection integrating multiple stress responses and playing an important role in metabolism-related diseases including DM. Here, we review the relationship between the ER and autophagy, inflammation, and apoptosis in DM to better understand the molecular mechanisms of this disease.